Philosophizing and being human : a textbook for senior high school - Calano, Mark Joseph T.; Pasco Marc Oliver D.; Ramoya, Marie Chris B. (Quezon City : Sibs Publishing House, Inc., 2016)
"We wrote a philosophy textbook that caters to high school students, meaning , it is a textbook meant for those who probably, after graduation, have plans other than going into philosophy as a college major." In this regard, every chapter of the book can rouse interest from the students that engages them from where they are-an excerpt from a poem or well-known song, a hypothetical scenario demanding a reaction, a brain teaser, among others. Afterward, every chapter will tackle at least three major themes that fall under the general topic. Each of the three discussions will involve some form of thought experiment or points for reflection that the students and teachers can use as a guide. Usually, an excerpt from a primary text will then follow so as to provide a kind of synoptic sweep of the three themes discussed."
Includes bibliography.
English text.
Keywords: Philosophical anthropology; Human behavior; Philosophy -- Textbooks